2018
DOI: 10.1016/j.ijheatmasstransfer.2018.04.101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of honeycomb porous plate on critical heat flux in saturated pool boiling of artificial seawater

Abstract: During a severe nuclear power plant accident, the integrity of the reactor pressure vessel must be assured. In response to a possible fuel meltdown, operators of the current generation of nuclear power plants are likely to inject water into the reactor pressure vessel to cool down the reactor vessel wall, preserving its integrity and avoiding leakage of radioactive material. This study considers the use of seawater to flood a reactor pressure vessel combined with the attachment of a honeycomb porous plate (HPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Various methods have been proposed for enhancing ERVC performance, including using structured surface, nanofluids (Pham et al, 2012;Angayarkanni and Philip, 2015) and thermal insulation (Yang et al, 2005;Noh and Suh, 2013). The structured surfaces include porous coating (Yang et al, 2006;Jun et al, 2016;Tetreault-Friend et al, 2016;Sohag et al, 2017;Wang et al, 2018), pin fins (Chu et al, 2013;Zhong et al, 2015), micro channels (Bai et al, 2016;Hou et al, 2017;Zhong et al, 2018aZhong et al, , 2018b, honeycomb porous plates (Mt Aznam et al, 2016;Fogaça et al, 2018), and spherical porous bodies (Mori et al, 2018), and so on. Yang et al (2006) fabricated a downward facing hemispherical surface with micro-porous coatings by sintering, while Sohag et al (2017) developed a Cold Spray technique to coat the same scale surface, both the coating surfaces were tested in the SBLB (Sub-scaled Boundary Layer Boiling) facility to investigate the CHF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been proposed for enhancing ERVC performance, including using structured surface, nanofluids (Pham et al, 2012;Angayarkanni and Philip, 2015) and thermal insulation (Yang et al, 2005;Noh and Suh, 2013). The structured surfaces include porous coating (Yang et al, 2006;Jun et al, 2016;Tetreault-Friend et al, 2016;Sohag et al, 2017;Wang et al, 2018), pin fins (Chu et al, 2013;Zhong et al, 2015), micro channels (Bai et al, 2016;Hou et al, 2017;Zhong et al, 2018aZhong et al, , 2018b, honeycomb porous plates (Mt Aznam et al, 2016;Fogaça et al, 2018), and spherical porous bodies (Mori et al, 2018), and so on. Yang et al (2006) fabricated a downward facing hemispherical surface with micro-porous coatings by sintering, while Sohag et al (2017) developed a Cold Spray technique to coat the same scale surface, both the coating surfaces were tested in the SBLB (Sub-scaled Boundary Layer Boiling) facility to investigate the CHF.…”
Section: Introductionmentioning
confidence: 99%
“…Mt Aznam et al (2016) investigated the CHF enhancement in combination with surface modification by attaching honeycomb porous plate (HPP) and nanoparticle deposition; the CHF of plain surface increases from 0.13 to 0.98 MW/m 2 with the inclination angle changing from 10° to 180°, while the CHF of structured surface was 1.51 to 1.75 MW/m 2 when the angle increased from 10° to 180°. Effect of HPP on CHF in saturated pool boiling of artificial seawater was studied by Fogaça et al (2018). They concluded that the CHF enhancement by HPP and nanoparticle deposition was the role of capillary action.…”
Section: Introductionmentioning
confidence: 99%